Uso de escórias de siderurgia no desenvolvimento e nutrição de gramíneas do gênero Brachiaria em um Latossolo Vermelho-Amarelo - Stocco, Fernando Carlos (2008)
The objective of this study was to evaluate the use of basic slag in mineral nutrition and development of Brachiaria brizantha and B. decumbens in soils in southern of the Espírito Santo. Samples were collected from a dystrophic Red Yellow Latossol, in an